Improving students' self-efficacy and academic performance in Applied Mathematics through innovative classroom-based strategy at Jimma University, Ethiopia - Kinde Getachew; Asfawossen Birhane (Universidad de Deusto, 2016)
Research on area of self-efficacy theory is scarce in African context though several scholars propose the need for investigating the practical utility of the theory in other cultural settings aside from Western countries. We have tested the theory of self-efficacy in Ethiopian context and showed how an innovative classroom based strategy (promoting students' mastery experience, exposing students to role model, persuading students the importance of effort and creating favorable attitude towards a subject) influenced self-efficacy belief and academic achievements of students in applied mathematics II employing explanatory sequential mixed methods design. We found statistically significant difference between the experimental group and the control group on mean academic performance of applied math II (t = 2.75, df = 121, p = .007). The magnitude of the mean difference (MD = 5.77) between the two groups was medium (η2 = .4978). There was no statistically significant mean difference in the experimental group and the control group on mean score of self-efficacy belief in mathematics (t = .626, df = 85, p = .553) though the experimental group scored higher than the control group. We validated the self-efficacy theory in Ethiopian context and also provided insight how mathematics instructors could use the innovative classroom based strategy. Further study on the applicability and generalization of the intervention package in other contexts is warranted.